The Effectiveness of Behavioral Counseling Theory and Relaxation Techniques to Improve Learning Concentration of 7th Grade Junior High School Students - Anak Agung Mella Widayanti; Luh Putu Sri Lestari; Kadek Ari Dwiarwati (Bisma The Journal of Counseling, 2025)
The low level of learning concentration experienced by students has become an obstacle to achieving optimal learning outcomes. Therefore, this study aims to examine the effectiveness of the behavioral counseling approach using relaxation techniques in improving the learning concentration of seventh-grade junior high school students. This research employed a quasi-experimental design with a nonequivalent control group design. The population in this study consisted of students from classes VII A1, VII A2, and VII A3 who had low learning concentration. The sample was selected using purposive sampling, involving 32 students from class VII A1. From these, 12 students with low concentration were chosen and divided into two groups: the experimental group and the control group. The data collection methods used were observation, interviews, questionnaires, and documentation. The research instrument was a questionnaire. Data were analyzed using the Independent Samples t-Test with the help of SPSS 26.0. The results showed that relaxation techniques within the behavioral counseling approach were effective in improving students’ learning concentration. Thus, Ha was accepted and H0 was rejected, indicating the effectiveness of the behavioral counseling approach with relaxation techniques in enhancing the learning concentration of seventh-grade junior high school students. These findings have important implications for the field of guidance and counseling, particularly in developing effective intervention strategies to address learning concentration problems at the junior high school level.